Hollow mesoporous architecture: A high performance Bi-functional photoelectrocatalyst for overall water splitting. (1st April 2018) - Shakeel, Muhammad; Arif, Muhammad; Yasin, Ghulam; Li, Baoshan; Khan, Arif Ullah; Khan, Faheem Ullah; Baloch, Musa Kaleem
Abstract: The metal/metal oxide and halide nanocomposites are emerging and effective photo/electrocatalyst to replace very expensive materials. These are remarkably preferred for efficient hydrogen production in energy conversion and storage technologies. Regardless of recent progress, their activity and durability are still far from adequate, due to less visible light effectiveness, wide band gape and high overpotential and low current density. Herein we successfully coupled a novel visible light accessible photo/electrocatalyst, silver-silver bromide doped hollow mesoporous silica-titania (Ag-AgBr/HMST). The syntheses of these composites were carried out using a facile one-pot micro-emulsification method at controlled calcination temperature. The results of the physicochemical characterization indicates that the composite obtained at optimal calcination temperature (550 °C), has exceptional morphology, high surface area, and uniformly distributed particles. These features exhibits the illustrious visible light induced photo/electrocatalytic behavior for overall water splitting. The hollow silica-titania provides incredible quality conducting channel, to get better mass loading and boost the charge transportation. While well-built connection of Ag, AgBr with titania, provides well active sites that accomplish obvious photo/electrocatalytic performance with OER current density of 10 mAcm −2 at 280 mV and HER current density of 65 mAcm −2 at −173 mV. This is almost equal to RuO2 and Pt/C that are very expensive catalyst for water oxidation. Therefore, the present work establishes the first example of hollow mesoporous photo/electrocatalyst for OER and HER water splitting. The outstanding durability prop up the use of mesoporous material for renewable energy application.